EXERCISE MODIFICATION TO ENHANCE LAYUP SHOOT ABILITIES IN BASKETBALL GAMES - Oriza Hardhina (International Journal of Basketball Studies, 2022)
Aim that research wants to try implementing modifications to the form of training to improve lay-up shoot movement skills in basketball games for extracurricular students at Gegesik 1 Public Junior High School, Cirebon Regency. The method used in this research is the experimental method. The research sample of 22 students. The type of instrument used to measure the lay-up shooting ability in basketball. Based on result, it can be concluded that the t-count values of the pre-test and post-test (15, 578, and 26.581) are greater than the t-table values with a df of 21 of 1.721 or t-count values of 26.581 > t-table 1.721) and 26,581 > 1,721, and the probability value is Sig. 0.00 0.05, so the alternative hypothesis in this study is accepted. Based on the results of the theoretical study and statistical tests that the authors have carried out, the authors draw the conclusion that there is a significant effect of training modifications on the lay-up shoot ability of basketball games in extracurricular activities of students